ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH PADA PERILAKU MANAJEMEN KEUANGAN KELUARGA (STUDI PADA RUMAH TANGGA DESA KALIANGET TIMUR) - Dessy Novitasari Laras Asih; very Andrianingsih (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2023)
The behavior of family financial management is fundamental to be considered by household financial managers. Finance is one of the most critical factors in the family. Family finance actors must be wise in applying it in everyday life. This study aims to determine family financial management carried out by the community. This study uses quantitative methods. The sampling technique in this study uses the accidental method. The independent variables used in this research are financial literacy, financial attitude, financial knowledge, financial experience, education level, and personality. The dependent variables used in this research are the behavior of family financial management. This study uses multiple linear regression analysis. The results of the research that has been carried out state that the variables that are significantly related are financial knowledge and financial experience. At the same time, financial literacy, financial attitude, education level, and personality are unrelated. Family financial management is influenced by financial knowledge and financial experience. This can reveal that good financial knowledge and financial experience can manage family finances properly.